2012
DOI: 10.1515/jpm.2011.113
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postpartum hypertension in women with twin pregnancies

Abstract: Antenatal blood pressure measurements and a laboratory work-up may be useful clinically for predicting postpartum hypertension in women with twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Our results clearly demonstrated that 67% of the cases with a diagnosis of GH or PE were recognized to have the disease during the intrapartum or postpartum period. Another study in Japan demonstrated that 40% of women without antenatal hypertension in twin pregnancy developed postpartum hypertension . A limitation of that report was a relatively small patient sampling and selection bias due to a heterogeneous population that contained more women with high risk referred at an advanced stage of gestation.…”
Section: Discussionmentioning
confidence: 97%
“…Our results clearly demonstrated that 67% of the cases with a diagnosis of GH or PE were recognized to have the disease during the intrapartum or postpartum period. Another study in Japan demonstrated that 40% of women without antenatal hypertension in twin pregnancy developed postpartum hypertension . A limitation of that report was a relatively small patient sampling and selection bias due to a heterogeneous population that contained more women with high risk referred at an advanced stage of gestation.…”
Section: Discussionmentioning
confidence: 97%
“…Women with twin pregnancies are more likely to develop hypertensive disorders, such as gestational hypertension, preeclampsia, and eclampsia, than women with singleton pregnancies [9,13]. Although the present 14 women with twin pregnancies did not develop hypertension during pregnancy, seven (50.0%) of the 14 women developed hypertension postpartum, consistent with the results of a recent study in which 60 (40%) of 150 women with twin pregnancies developed postpartum hypertension [13]. Thus, women with twin pregnancies are prone to the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Twin pregnancy differs considerably from singleton pregnancy in many aspects, such as the duration of pregnancy [11], the degree of enhancement of coagulation-fibrinolysis [14], the prevalence of pregnancy-induced hypertension [13,9], and the degree of blood volume expansion [15]. All these data suggest that pregnancy-induced changes in various biological and physiological parameters may be greater in women with twin pregnancies than in women with singleton pregnancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twin pregnancy differs considerably from singleton pregnancy in many aspects, such as the duration of pregnancy [1], the degree of enhancement of coagulation-fibrinolysis [2], the prevalence of pregnancy-induced hypertension [3,4], changes in plasma aldosterone and renin activity [5], and the degree of blood volume expansion [6]. These data suggest that pregnancy-induced changes in various biological and physiological parameters may be higher in women with twin pregnancies than in those with singleton pregnancies.…”
Section: Introductionmentioning
confidence: 99%